Green behavior and sustainable consumption: a gratifying conclusion of environmental movement - Hosseinpour, Masoumeh; Nezakati, Hossein; Md Sidin, Samsinar; Wong, Foong Yee (Universiti Putra Malaysia Press, 2016)
Earth is currently facing severe degradation, from global warming, ozone layer depletion, and large scale pollution among other causalities. Majority of these depredating forces have been traced back to exploitive human behaviors (UNEP, 2012). However, the environmental movement which was developed to protect the environment against such exploitive human actions, demands a change in our behavior towards the environment. The increasing awareness brought upon consumers by this movement, on the effect of our behavior on the environment, (Jackson 2005) which supports the adoption of environment friendly behavior. The concern over environmental degradation as a movement, first started in the United States of America (U.S.A), Europe, and then Asia. In United States of America, the movement appeared for the first time during the 1960s and 1970s, partially after experiencing the drawbacks from use of modern technology, and the first oil crisis (Grunert and Juhl, 1995). During the twentieth century, several environmental groups made attempts to create awareness among public on environmental conservation. For instance, Rachel Carson’s bestseller book entitled “Silent Spring” focused on the hazardous effects of application of DDT (Dichlorodiphenyltrichloroethane) and other human activities on the ecosystem and the environment (Carson, 1962). The author attempted to explain how each and every human activity had a direct or indirect effect on the food chain, its ecosystem, and ultimately the environment. The observations made by Rachel Carson were supported by then President of the United States of America, President John F. Kennedy, who acknowledged the importance of her book and environmental movement for the nation and the world.